Comments on Mr. Johnson's Notes - Robertson, D. H. (Review of Economic Studies, 1951)
Journal Article Comments on Mr. Johnson's Notes Get access D. H. Robertson D. H. Robertson Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 19, Issue 2, 1951, Pages 105–110, https://doi.org/10.2307/2295738 Published: 01 July 1951